Avaliação das alterações comportamentais e neuroquímicas em camundongos submetidos ao modelo neurodesenvolvimental de esquizofrenia induzido por dois desafios: estudo da influência do sexo - Silva, Francisco Eliclécio Rodrigues da (2021)
Schizophrenia is a serious mental disorder that affects more than 21 million people worldwide and is associated with a set of symptoms grouped into positive, negative and cognitive. Evidence shows that this pathology involves changes in brain circuits that may be related to two critical moments of synaptic pruning (perinatal period and adolescence - neurodevelopmental hypothesis). The two-hit model adopted in the present study simulates this situation through perinatal infection with Poly I: C (PIC), a synthetic double-stranded RNA analog that mimics a viral infection stimulating a response via cytokines, combined to unpredictable stress in adolescence. The incidence of schizophrenia is generally higher in males than in females, with a ratio of 1.4:1 (male: female). This fact occurs due to the potential neuroprotective effect caused by estrogen, which supports the “estrogen hypothesis”. Besides the difference in symptoms between men and women, variations can be observed in the course of the disease and in the phase of the estrous cycle in females, as well as in the pharmacological treatment. Thus, using the two-hits model in mice, the present study aimed to investigate the influence of sex on behavioral changes (through the pre-pulse inhibition, Y maze and social interaction tests), as well as to evaluate the expression of related proteins schizophrenia in the hippocampus, striatum and prefrontal cortex (parvalbumin, α7-nAChR, phospho-NR2B and DRD2), as well as determining changes in metabolic pathways (kynurenine pathway) and expression of enzymes related to estrogen signaling (GPER, ERα, ERβ, TSPO and Aromatase). The model induced positive, cognitive, and negative symptoms in male and female animals in diestrus. Furthermore, males showed a higher deficit of negative symptoms. In male animals an increase in the expression of DRD2 (striatum) and NR2B (PFC) in animals challenged only in adolescence was also observed. In diestrus females it was observed a decrease in parvalbumin (striatum) and α7-nAChR (PFC) in animals exposed to both challenges (PIC + (S)), and in proestrus females it was noted an increase in these both proteins when they were exposed only to stress in adolescence. The males exposed to both challenges also presented an increase in the expression of KYNU, KAT and ACMSD with a decrease in tryptophan and an increase in quinolinic acid were also observed. In diestro females, also exposed to both challenges, an increase in KYNU and KAT was noticed with no significant changes in proestrus females. Males exposed to both challenges also had a decrease in GPER, ERα, ERβ, TSPO and aromatase. Proestrus females exposed to both challenges had an increase in GPER, TSPO and aromatase without significant changes in diestrus females. Our results lead to a possible neuroprotective effect of estrogen, considering that females in proestrus did not show schizophrenia-like symptoms caused by the model.